Numerical modelling of intergranular fracture in polycrystalline materials and grain size effects - M. Paggi; P. Wriggers (Fracture and Structural Integrity)
In this paper, the phenomenon of intergranular fracture in polycrystalline materials is investigated using a nonlinear fracture mechanics approach. The nonlocal cohesive zone model (CZM) for finite thickness interfaces recently proposed by the present authors is used to describe the phenomenon of grain boundary separation. From the modelling point of view, considering the dependency of the grain boundary thickness on the grain size observed in polycrystals, a distribution of interface thicknesses is obtained. Since the shape and the parameters of the nonlocal CZM depend on the interface thickness, a distribution of interface fracture energies is obtained as a consequence of the randomness of the material microstructure. Using these data, fracture mechanics simulations are performed and the homogenized stress-strain curves of 2D representative volume elements (RVEs) are computed. Failure is the result of a diffuse microcrack pattern leading to a main macroscopic crack after coalescence, in good agreement with the experimental observation. Finally, testing microstructures characterized by different average grain sizes, the computed peak stresses are found to be dependent on the grain size, in agreement with the trend expected according to the Hall-Petch law.